Psychopathy Incorporated - Koenraad Priels (University of Darussalam Gontor Press, 2023)
The purpose of this paper is to provide a qualitative structural analysis of capitalism and demonstrate that it needs to be defined as a “psychopathic system.” Its inherent structural dynamics violently centralize and concentrate wealth and ideological and political power in the hands of a “psychopathic ruling class” with callous disregard for the resulting socio-ecological destruction. For epistemological clarity and clinical, criminological accuracy, global capitalism should be defined as “Psychopathy Incorporated.” Critical realism becomes a discipline of humane self-defense against psychopathy in power. Perpetuating capitalism proves to be demonstrably clinically and criminally insane. From a rational, humanitarian perspective, the radical solutions to our contemporary predicament are to fully acknowledge the trans-historical problem of psychopathy in power, criminalize capitalism and humanize socio-economic structures.